Influence of the myotome zone and sex on the muscle cellularity and fillet texture of diploid and triploid turbots Scophthalmus maximus L. - Ayala, María Dolores; Hernández-Urcera, Jorge; Santaella, Marina; Martínez Graciá, María Carmen; López-Albors, Octavio; Cal, Rosa (Urmia University, 2020)
8 pages, 4 tables, 1 figure.-- This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License The muscle and textural parameters were analyzed in four myotome zones (epaxial upper, hipoaxial upper, epaxial bottom, and hipoaxial bottom) in seven diploids (D) and seven triploids (T) turbot specimens. Diploid specimens showed the highest values of the size and number of white fibers in the epaxial zones, being such values higher in female than male specimens. In triploid specimens, the highest fibers sizes were found in the upper zones (epaxial and hipoaxial), whereas the lowest number and density of fibers were found in the epaxial upper zone. In this latter group (T), the lowest fibers sizes were found in female specimens, whereas the rest of the parameters were usually higher in female than male specimens. When comparing both groups, the hypertrophy was higher in T than D in all zones. In both ploidy groups, the highest textural values were usually observed in the upper epaxial fillet, being slightly higher in female than male specimens. The values of standard length, total weight, gonad weight, gonadosomatic index and gutted weight were higher in female than male specimens in both groups (D and T) JHU is supported by a Juan de la Cierva’s post-doc research grant (# FJCI-2016-30990) funded by the Spanish Ministry of Science, Innovation, and Universities Peer reviewed